The American Society for Clinical Pathology's 2021 Wage Survey of Medical Laboratories in the United States. Issue 6 (5th October 2022) - Garcia, Edna; Kundu, Iman; Fong, Karen
Abstract: Objectives: To inform the pathology and laboratory field of the most recent national wage data. Historically, the results of this biennial survey have served as a basis for additional research on laboratory recruitment, retention, education, marketing, certification, and advocacy. Methods: The 2021 Wage Survey was conducted through collaboration between the American Society for Clinical Pathology (ASCP) Institute of Science, Technology, and Policy in Washington, DC, and the ASCP Board of Certification in Chicago, IL. Results: Compared with 2019, results show that mean hourly wage for staff-level personnel increased for only two occupations—cytologist and medical laboratory scientist/medical technologist/clinical laboratory scientist—after adjusting for inflation. Geographically, laboratory professionals from urban areas continue to earn more than their rural counterparts. Most respondents reported no change in their salaries during the coronavirus disease 2019 pandemic. Conclusions: The pandemic had a significant effect on staffing, workload, and work-life balance of many laboratory professionals. Even with the salary increases reported from the results of this survey, it is evident that the increases have not kept up with the current inflation. Focus on visibility, recruitment and retention, and diversity are essential to develop long- and short-term solutions.